Rehabilitation of executive functioning in patients with frontal lobe brain damage with goal management training. - ROBERTSON, IAN H (My University, 2011)
Executive functioning deficits due to brain disease affecting frontal lobe functions cause significant real-life disability, yet solid evidence in support of executive functioning interventions is lacking. Goal Management Training (GMT), an executive functioning intervention that draws upon theories concerning goal processing and sustained attention, has received empirical support in studies of patients with traumatic brain injury, normal aging, and case studies. GMT promotes a mindful approach to complex real-life tasks that pose problems for patients with executive functioning deficits, with a main goal of periodically stopping ongoing behavior to monitor and adjust goals. In this controlled trial, an expanded version of GMT was compared to an alternative intervention, Brain Health Workshop that was matched to GMT on non-specific characteristics that can affect intervention outcome. Participants included 19 individuals in the chronic phase of recovery from brain disease (predominantly stroke) affecting frontal lobe function. Outcome data indicated specific effects of GMT on the Sustained Attention to Response Task as well as the Tower Test, a visuospatial problem-solving measure that reflected far transfer of training effects. There were no significant effects on self-report questionnaires, likely owing to the complexity of these measures in this heterogeneous patient sample. Overall, these data support the efficacy of GMT in the rehabilitation of executive functioning deficits.
PUBLISHED
Keywords: Neuroscience; frontal lobe; traumatic brain injury